Case report: Coexistence of triple-seronegative myasthenia gravis and pathology-proven cryptogenic organizing pneumonia - Huang, Shi-Qi; Wang, Bin; Gao, Lin; Wang, Meng; Zhao, Hong-Dong; Shi, Jian-Quan (Frontiers in Neurology, 2023)
Objective Emerging evidence shows that patients with myasthenia gravis (MG) were at a higher risk for the co-occurrence of other autoimmune diseases, which reflects phenotypic heterogeneity in MG. The coexistence of MG and cryptogenic organizing pneumonia (COP) has rarely been reported. The present case is to report the coexistence of triple-seronegative MG and pathology-proven COP in a patient. Methods The clinical data of the patient were derived from medical records of Nanjing First Hospital, Nanjing Medical University, China. Written informed consent was obtained from the patient. Results We presented a 56-year-old man with acute respiratory syndrome, who was diagnosed with COP based on the intra-alveolar fibroinflammatory buds (Masson's bodies) in the pathology of bronchoscopy biopsy. Oral prednisone induced dramatic symptomatic improvement and complete resolution of previous lung lesions. After a stable course of no respiratory symptom for 2 months, he was referred to the neurology department with complaints of fluctuating generalized muscle weakness. He was diagnosed with triple-seronegative MG based on fluctuating weakness, neostigmine test-positivity and RNS-positivity. After three-month treatment with pyridostigmine in combination with tacrolimus, the symptoms gradually improved and he achieved minimal symptom expression. Conclusions This case highlights the rare coexistence of triple-seronegative MG and pathology-proven COP. However, a causal association between COP and MG cannot be explicitly ascertained. In future, more data are needed to clarify the relationship, taking into account the limited number of cases reported with this coexistence of the diseases.